DIFFERENCES IN THE PREVALENCE OF BLOOD PRESSURE CONDITIONS USING ESH VS AAP GUIDELINES IN CHILDREN AND ADOLESCENTS. (June 2018) - Lurbe, E.; Torro, M.I.; Aguilar, F.; Redon, J.; Alvarez-Pitti, J.; Redon, P.
Abstract: Objective: The objective is to assess differences in the prevalence of blood pressure (BP) conditions according to the European Society of Hypertension (ESH) guidelines (Lurbe, J Hypertens 2016) and the American Academy of Pediatrics (AAP) (Flynn, Pediatrics 2017) in children and adolescents. Design and method: Four thousand two hundred and ninety-six Caucasians of both sexes (1941 females), of European origin, from 5 to 18 years of age (mean age 11.5 3.3) in the absence of antihypertensive treatment were included. Overweight and obesity (n = 2243) were defined based on the extended international body mass index cut-offs. Office BP was measured in the non-dominant arm with cuff and bladder size adjusted to upper-arm girth. The three measurements of each office visit were averaged for analysis. Twenty-four-hour ambulatory BP monitoring was performed by using Spacelabs monitor 90207. Subjects were qualified as true normotensive (N), white-coat (WC), masked (M) or sustained hypertensive (HTN) according to the ESH and AAP criteria for office BP, and reference values for 24-hour ambulatory BP (Wühl, J Hypertens 2002). Results: The prevalence of N, WC, M and HTN were significantly different when the ESH or AAP were applied. Overall, the largest differences were observed in the prevalence of WC, which was double when the AAP criteria were used. The differences were larger for boys, older than 13 years of age. The presence of obesity did not reduce the higher prevalence of WC by the AAP criteria. In contrast, M was slightly higher when the ESH criteria were applied. The impact on the prevalence of WC and M is shown in the figure. Figure. No caption available. Conclusions: When applying the AAP criteria, compared with that of the ESH, the main difference is the higher prevalence of WC, especially in boys aged 13 years or older. The consequence is an increment of the HTN work-up in children and adolescents.